Remembering communism : private and public recollections of lived experience in Southeast Europe - Dimou, Augusta; Todorova, Marii͡a Nikolaeva; Troebst, Stefan (Leipzig studies on the history and culture of East-Central Europe, 2014)
"The volume examines the formation and transformation of the memory of communism in the post-communist period. The majority of the articles focus on memory practices in the post-Stalinist era in Bulgaria and Romania, with occasional references to the cases of Poland and the GDR. Based on an interdisciplinary approach, including history, anthropology, cultural studies and sociology, the volume, examines the mechanisms and processes that influence, determine and mint the private and public memory of communism in the post-1989 era. Common denominator to all essays is the emphasis on the process of remembering in the present, and the modalities by means of which the present perspective shapes processes of remembering, including practices of commemoration and representation of the past. As a result, the analyses point at the sociopolitical factors and societal processes that help construct, transform, stabilize and finally canonize past memory. Due to its interdisciplinary character and the wide range of methodological and theoretical approaches presented, the volume offers a broad and varied kaleidoscope of memorial practices in a variety of milieus of post-communist societies, from school to the internet. The volume deals with eight major thematic blocks revisiting specific practices in communism such as popular culture and everyday life, childhood, labor, the secret police, the perception of 'the system' and others. The analyses highlight occasionally similarities and differences between the two principal case studies, resulting in the end effect in the observation of a significant divergence in the memory of communism between the two neighboring countries"--Provided by publisher